Improvement of Nutritional Status in Liver Cirrhotic Patients with Adequate Dietary Feeding and High Branched-chain Amino Acids Supplementation - Suzanna Ndraha; Marcellus Simadibrata (The Indonesian Society for Digestive Endoscopy, 2012)
Background: There is still a high prevalence of malnutrition among liver cirrhotic patients despite the fact that it deteriorates their prognosis. Pre-albumin can be used as a parameter to evaluate short-term nutritional status. This study was conducted to find out the overall outcome of calories and protein diet, and substitution of branched-chain amino acids (BCAA) to enhance pre-albumin serum level in cirrhotic patients with malnutrition. Method: This was a quasi-experimental study conducted in liver cirrhotic patients who visited Koja Hospital between April and September 2009. Mid-arm muscle circumference (MAMC) was used to evaluate nutritional status. Those with MAMC below the 15th percentile were considered as malnourished. Diet of adequate calories and protein with the substitution of 2 x 4 scoop (± 60 g) BCAA milk powder in 200 mL warm water twice daily (± 7.3 g BCAA) was given for two weeks. Pre-albumin serum level was subsequently monitored (before and after intervention) to see if there were any nutritional status changes. Data was analyzed using dependent student T-test with SPSS version 15.0. Results: There were eligible 16 patients. The average pre-albumin level after diet intervention for two weeks was significantly higher than those before the intervention; i.e. from 5.8 (2.2) mg/dL to 6.8 (2.1) mg/dL, with p = 0.004. Conclusion: Diet of adequate calories and branched-chain amino acid can improve the pre-albumin serum level in liver cirrhotic patients with malnutrition. Keywords: cirrhosis, malnutrition, pre-albumin, BCAA